O julgamento de sentenças metafóricas do Português Brasileiro: uma proposta de análise por meio de testes não cronométricos - Martins, Maria Clara Machado (2021)
Metaphors have been the object of study by several authors, who, in great majority, debate whether metaphors are understood as comparisons or categorizations; in observing the relationship between similarity and metaphor; in analyzing how metaphors differ from literal statements; whether they are processed directly or indirectly, whether they are processed in two or three stages. In this work, encompassed by the area of Experimental Psycholinguistics, the objective was to verify if the indexes of “familiarity”, “conventionality” and “aptness” of metaphors influence the judgment, that is, the comprehension of metaphorical sentences in Brazilian Portuguese, through images. The specific objectives were: 1) to identify “familiar”, “very conventional” and “very apt” metaphors and; 2) to verify, through images, the influence of “familiarity”, “conventionality” and “aptness” in the judgment of sentences metaphorical. There were four hypotheses: 1) a metaphor is comprehended if it is conventional for the participant, regardless of the “familiarity” and “aptness” indices; 2) the “familiarity” and “aptness” indexes are directly related, that is, the higher the “familiarity” index, the higher the “very apt” and “aptness” index; 3) for metaphors with higher indexes of “familiarity”, “conventionality” and “aptness”, images that evidence the metaphorical meaning will be selected by the participants; and 4) for metaphors with lower indexes, images that evidence the literal meaning will be selected by the participants. This research is theoretically based on authors such as Searle (2005[1979]), Finger (1996), Glucksberg (2003), Bowdle and Gentner (2005), among others. The methodology of this work had two stages of data collection, in the first stage they were made available as Tasks 1 and 2, and in the second stage, Task 3. The three Tasks were distributed online, through the platform JotForm. The metaphors used in this work were taken from Lakoff and Johnson (2002[1980]). For tasks 1 and 2 were presented ten metaphors. For Task 3, from the analysis of the first two tasks, six metaphors were selected, later divided into two groups: three metaphors with the highest rates of “familiarity”, “conventionality” and “aptness” (Group 1) and three metaphors with the lowest rates (Group 2). In Task 3, for each sentence, there were three images as alternatives and the participants had to choose one image among the three. With the answers from Task 3, intra and intergroup analyzes were performed, using the chisquare test for independence. In the intragroup analysis (both for Group 1 and Group 2), when verifying the metaphorical sentences, we realize that there is a statistically significant difference (p < 0.01) regarding the choice of the image selected by the participant – if an image that evidences the metaphorical meaning or image that evidences the literal meaning. For an intergroup analysis, however, no statistical significance was observed (p = 0.07). That is, the significance was verified only within the groups and, in addition, we also observed that in both groups were selected the images that evidence the metaphorical meaning. From the results observed in this study, it is possible to affirm that the indices of “familiarity”, “conventionality” and “aptness” are not sufficient to point out influence in the judgment of metaphorical sentences, through images, since, as seen in intra and intergroup analyses, regardless of the indexes selected for observation, the participants selected images that show the metaphorical meaning.